KAJIAN FAKTOR-FAKTOR YANG MEMPENGARUHI PILIHAN INOVASI PERTANIAN PERKOTAAN DI WILAYAH JAKARTA SEKITARNYA - Astrina Yulianti,STP, MM; Yovita Anggita Dewi; ume humaedah; maesti mardiharini (Jurnal Pengkajian dan Pengembangan Teknologi Pertanian, 2019)
The Study of Influencing Factors on The Decisions of Urban Farming’s Innovation in Jakarta and its Nearby Cities. Urban farming has begun to be widely known and interested by urban communities. In Indonesia, its development has considered as one of the food security efforts. Limitations on land and management skills became the basis of government programs by the Ministry of Agriculture to disseminate urban farming innovations, particularly in Jakarta  by running the three of dissemination models consist of “Agro-park and Innovation-mart” (Tagrimart/TA), Extension Communication (KP) and Bio-industry (BI). The study aimed to determine the factors that influenced the decissions of urban farming innovation which were applied through three models of dissemination and the modifications that were carried out as creativities after the implementation of urban farming innovation. Jakarta and its nearby cities were selected as study area. Data was collected during October-November 2016. Analysis of the study was generated using correlation tests, multiple linear regression, and ordinal regression of 14 variables. Factors significantly influenced the number of applied innovation were dissemination channels, perception of the roles of urban farming, as well as knowledge and skills. Futhermore, the number of applied innovation became a significant influenced factor to creativity (the ability in modifying innovation).   Pertanian perkotaan mulai banyak dikenal dan diminati masyarakat urban. Pengembangannya di Indonesia dianggap bagian dari upaya mewujudkan ketahanan pangan rumah tangga. Keterbatasan lahan dan keterampilan pengelolanya menjadi landasan program pemerintah khususnya Kementerian Pertanian untuk mendiseminasikan inovasi pertanian perkotaan, untuk wilayah Jakarta melalui model diseminasi Taman Agro dan Agro Inovasi mart (Tagrimart/TA), Komunikasi Penyuluh (KP), dan Bioindustri (BI). Kajian ini bertujuan mengetahui faktor-faktor yang mempengaruhi pilihan inovasi pertanian perkotaan yang diterapkan melalui tiga model diseminasi tersebut. Jakarta dan sekitarnya dipilih sebagai lokasi kajian. Data dikumpulkan pada bulan Oktober-November tahun 2016. Analisis dilakukan menggunakan uji korelasi, regresi linear berganda, dan regresi ordinal terhadap total 14 variabel. Faktor-faktor yang berpengaruh signifikan terhadap jumlah inovasi yang diterapkan terdiri dari: saluran diseminasi, persepsi terhadap peran pertanian perkotaan, serta pengetahuan dan keterampilan. Lebih lanjut, faktor jumlah inovasi yang diterapkan memberikan pengaruh signifikan terhadap kreativitas (kemampuan dalam modifikasi inovasi).